Fisheries and Fishing - Sackel, Johanna (The Routledge Handbook on the Economic History of Natural Resources)

Ressourcenräume: Seerecht, Geopolitik und Wissenschaftsdiplomatie zwischen den Seychellen, Frankreich und der Bundesrepublik Deutschland um 1980 - Kunkel, Sönke; Sackel, Johanna (Räume in der Internationalen Geschichte)

Räume in der Internationale Geschichte

Wem gehört das Meer? Globale Ressourcen und die dritte UN-Seerechtskonferenz (1968–1994) - Sackel, Johanna

Networks - Sackel, Johanna; Wöbse, Anna-Katharina (A Cultural History of the Sea in the Global Age)

Solidarität vs. Ressourcensouveränität? Die dritte Seerechtskonferenz als Herausforderung für die Süd-Süd-Beziehungen - Sackel, Johanna (Nord/Süd Perspektiven auf eine globale Konstellation)

„Rationale Fischerei“? Das Konzept des Maximum Sustainable Yield im Spannungsfeld von Ökonomie und Ökologie - Sackel, Johanna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

Tagungsbericht: Globale Ungleichheiten diskutieren — Der Nord-Süd-Konflikt in den internationalen Beziehungen - Sackel, Johanna

Food justice, common heritage and the oceans: Resource narratives in the context of the Third United Nations Conference on the Law of the Sea - Sackel, Johanna (International Journal of Maritime History)
The United Nations Conference on the Law of the Sea was an arena in which global resource equity was negotiated in a process that extended beyond the governmental actors who took centre stage. But our perceptions of the role of an increasingly civil society in framing national decision-making processes during the 1970s – for instance, through trade associations or nongovernmental organizations – is blurred. Both civil society and economic actors crafted similar policies, though for different purposes: some – with regard to the north–south divide – focused on the conservation of the ocean’s resources over the long term, whereas others were more concerned with short-term economic benefits. This article asks which arguments legitimized property and usage rights, and which resource narratives were used. By taking into account the charged relationship of local–national–global reaches, it also examines perceptions and management of resources in the context of resource equity on a global scale.
Keywords: Transportation; History